Protecting Batik Customers and the Existence of Pekalongan Original Batik by Augmented Reality Technology Based on Cloud Computingin Batik Label - Christianto, Paminto Agung; Susanto, Eko Budi; Kurniawan, Ichwan (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2017)
The wrong assumption stating batik printed textilebatik issimilar withoriginal batik bears a loss for batik producers, because customers tend to buy printed textilewhich are cheaper than originalones (“tulis”, “cap” or “combination” batik). The misperception used by some batik enterpreneurs who mentioned that products he sold arekinds of original batik, although theyare printed textile. It disrupts the existence of Pekalongan traditional batikas well andmany customers experience losses. This research is an effort to support Indonesian government in maintaining batik as an Indonesian cultural heritage, and Pekalongan city government in maintaining the existence of